Reversible impairment of the ku80 gene by a recyclable marker in Aspergillus aculeatus - Tani, Shuji (Springer, 2013)
Auxotrophic mutants of Aspergillus can be isolated in the presence of counter-selective compounds, but the process is laborious. We developed a method to enable reversible impairment of the ku80 gene (Aaku80) in the imperfect fungus Aspergillus aculeatus. Aaku80 was replaced with a selection marker, orotidine 5’-phosphate decarboxylase (pyrG), followed by excision of pyrG between direct repeats (DR) to yield the Aaku80 deletion mutant (MR12). The gene-targeting efficiency at the ornithine carbamoyltransferase (argB) locus was drastically elevated from 3% to 96% in MR12. The frequency of marker recycling depended on DR length. One uridine auxotroph was obtained from 3.3 × 10(5), 1.4 × 10(5), and 9.2 × 10(3) conidia from strains harboring 20-, 98-, and 495-bp DRs, respectively. Because these strains maintained the short DRs after 5 d of cultivation, we investigated whether Aaku80 function was disrupted by pyrG insertion with the 20-bp DR and restored after excision of pyrG. The Aaku80 disruption mutant (coku80) was bred by inserting pyrG sandwiched between 20-bp DRs into the second intron of Aaku80, followed by excision of pyrG between the DRs to yield the coku80rec strain. Analyses of homologous recombination frequency and methyl methanesulfonate sensitivity demonstrated that Aaku80 function was disrupted in coku80 but restored in coku80rec. Furthermore, pyrG was maintained in coku80 at least for ten generations. These data indicated that reversible impairment of ku80 in A. aculeatus is useful for functional genomics in cases where genetic segregation is not feasible.